Freestyle sports and Olympic games - A governance analysis of international freestyle snowboarding - Strittmatter, A.-M.; Kilvinger, B. (6. Innsbrucker Sportökonomie & management Symposium - Book of Abstracts, 2016)
This article shows which impact this decision of IOC has on the organizational structures of a freestyle sport on national and international level which resulted in the case of freestyle snowboarding in an inefficient overall environment and lead to negative consequences on the sport itself. Other freestyle sports under discussion to be incorporated into the Olympic program such as surfing and skateboarding can learn from the process that snowboarding underwent in order to avoid facing a fragmente d governance of the sport. Since the members of competitive freestyle snowboarding organizations are at a large amount similar, it is possible to work towards a more efficient structure on international level. We propose future research on the governance of freestyle sports to extent this thought, focusing on possible organizational structures for IFs that are accepted by both, the respective actions sports and the IOC and which can develop, administer, and govern freestyle competitions on all levels. As well, the influences of both industry and nation based system on the athlete management could be interesting to look at. In sum, we have provided a step in the research into the governance of new sports with other history and culture - hence different structures - than the established Olympic sports.